2017
DOI: 10.1016/j.chemosphere.2016.10.091
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of soil arsenic release by human gut microbiota and its intestinal absorption by Caco-2 cells

Abstract: Arsenic (As) speciation is essential in assessing health risks from As-contaminated soil. Release of soil-bound arsenic, As transformation by human gut microbiota, and the subsequent intestinal absorption of soil As metabolites were evaluated. A colon microbial community in a dynamic human gut model and the intestinal epithelial cell line Caco-2 were cultured. Arsenic speciation analysis and absorption of different As species were undertaken. In this study, soil As release (3.7-581.2 mg kg) was observed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…To our knowledge, this was the first ever report of the bioaccessibility of Cu, Fe, Mn, and Zn in the market vegetables in the colon, which suggested that the previous in vitro studies without simulating the colon phase could have overestimated the bioaccessibility and bioavailability of Cu while underestimated those of Fe, Mn, and Zn. Under the anaerobic environment of the colon, human gut microbiota could induce reductive dissolution of Fe and Mn 22 , although the secondary Fe/Mn (hydr)oxides formation could inhibit their dissolution 18 , 28 . Besides, these trace metals present as organometallic salts in vegetables could be nutritional supplementation to the gut microbiota, resulting in their further release in the colon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this was the first ever report of the bioaccessibility of Cu, Fe, Mn, and Zn in the market vegetables in the colon, which suggested that the previous in vitro studies without simulating the colon phase could have overestimated the bioaccessibility and bioavailability of Cu while underestimated those of Fe, Mn, and Zn. Under the anaerobic environment of the colon, human gut microbiota could induce reductive dissolution of Fe and Mn 22 , although the secondary Fe/Mn (hydr)oxides formation could inhibit their dissolution 18 , 28 . Besides, these trace metals present as organometallic salts in vegetables could be nutritional supplementation to the gut microbiota, resulting in their further release in the colon.…”
Section: Resultsmentioning
confidence: 99%
“… 12 and Yin et al . 22 . Briefly, the fresh vegetable sample (3 g) in triplicate was added to a polypropylene conical centrifuge tube (50 mL) with the digest (30 mL) at a solid/solution (s/s) ratio of 1:10 in the gastric and small intestinal phases.…”
Section: Methodsmentioning
confidence: 99%
“…The same authors using SHIME, analyzed the interactions between four soils with different As concentrations and fecal microorganisms, demonstrating that human GM can release soil-bound As. In humans subjected to soil As exposure, an precise risk assessment could be carried out by concurrently defining As transformation and intestinal absorption (46).…”
Section: Arsenicmentioning
confidence: 99%
“…Furthermore, As metabolism by human gut microbiota and intestinal absorption of these As metabolites should be concurrent processes. Intestinal absorption of different As standard species or metabolites is examined using in vitro studies with the Caco-2 human cell line of human colon carcinoma (Hinrichsen et al, 2015;Yin et al, 2017). In short, methylated trivalent arsenicals display a higher transport across epithelial cells in comparison with inorganic arsenic and the methylated pentavalent species.…”
Section: Introductionmentioning
confidence: 99%